MARITAL RAPE SEBAGAI SUATU KEKERASAN DALAM RUMAH TANGGA DALAM PRESPEKTIF HUKUM ISLAM DAN POSITIF INDONESIA - Litya Surisdani Anggraeniko; Dede Kania; Usep Saepullah (Asy-Syari'ah, 2022)
Abstract: The practice of marital rape or known as marital rape is a discussion that is often considered a contradictio in terminis which is interpreted as a combination of contradictory words, because currently rape is limited outside marriage. Rape in marriage is a form of inequality in gender justice, the assumption is that men/husbands have an autonomous right to force their wives to have sex, while women/wives are legitimized by construction to devote themselves to accepting whatever is done in marriage. This should not be in line with what has been regulated in the Marriage Law, which basically states that the purpose of marriage is to form a happy and eternal family (household) based on the One Godhead. Marital rape can be defined as coercion of sexual activity by one party without regard to the other party. The purpose of this study is to explain the basis for regulating marital rape in positive law in Indonesia and Islamic law. The research method used is juridical-normative, namely research by analyzing the provisions of laws and regulations relating to marital rape by connecting the basic arrangements in Islamic law. The results of this study indicate that domestic rape or known as marital rape is part of sexual violence in the household as regulated in the PKDRT Law. Meanwhile, in Islam the essence of marriage is interpreted as mistaqan ghalidzan or a sacred and strong bond, then the practice of forced sexual intercourse is considered an inequality of rights and obligations of sexual relations in marriage. Islam teaches the principle of mu'asyarah bil ma'ruf, namely a good and voluntary relationship. in having sexual relations by not monopolizing sexuality in the name of religion because it is clearly against the Shari'a.